Separation index and fit items of creative thinking skills assessment - Andi Ulfa Tenri Pada; Badrun Kartowagiran; Bambang Subali (REID (Research and Evaluation in Education), 2016)
This article discusses the evaluation results of the separation index and fit item of creative thinking skills assessment that supports the conation aspect of prospective biology teachers in Aceh. This assessment consists of 37 items of divergent tasks, which is the application of human physiology courses that support the conation aspects. The participants were selected from the Biology Education Program, Faculty of Teacher Training and Education, Syiah Kuala University. The data were analyzed using the Quest software including the separation index and fit item. The results indicate that the creative thinking skills assessment instrument that supports the conation aspect of prospective biology teachers has a good separation index and all the items fit PCM-1PL.